The Burning Monk: A Review of a Buddhist's Self-Immolation during the Vietnam War - Benedičič, Luka (Poligrafi, 2022)
This paper is a study of the self-immolation of the Mahayana Buddhist monk Thich Quang Duc in 1963, Saigon. It highlights some of the reactions to this event, as well as more recent academic analyses, and contrasts them with the letter of the monk Thich Nhat Hanh who disagreed that the self-immolation was a protest or suicide. This ontological discrepancy motivated new research approaches. In order to show it as studyable, the paper thematizes it by introducing the conceptual pair of visible-invisible. It presents a discussion by Mario Blaser that addresses the field of epistemology and ontology, also commenting on some fundamental theoretical approaches such as the ontological turn and cosmopolitics. The paper argues that the invisible – for example ontological – contents of the event have been overlooked in many analyses, or oversimplified by using an objectivist or political vocabulary.